Teaching creative thinking developing learners who generate ideas and can think critically - Lucas, Bill 1956-; Spencer, Ellen (Pedagogy for a changing world., 2017)
'Teaching Creative Thinking' explores the ways in which teachers can help learners to cultivate the dispositions which evidence suggests are going to be valuable to them both at school and in later life. Creative thinking is original, purposeful and valuable. In many ways, creative thinking is a social activity and it usually takes place in response to an issue or problem facing an individual or group. Creative thinkers are inquisitive, collaborative, imaginative, persistent and disciplined: all key abilities that schools can help learners to develop